Nutrition Education Programmes In Himachal Pradesh - Sharma Monica; Sobti Renu; Saxena Rita (Wolters Kluwer Medknow Publications, 1986)
A study of development programmers in Himachal Pradesh revealed that nutrition education is imparted through 24 different programmes. Various Channels of communication are used. Supplementary nutrition programmes which presently do not include nutrition education have been identified. All opportunities for nutrition education require to be exploited. The support for nutrition education activities, in terms of money and materials, was found to be inadequate.